Social Reactions to IPV Disclosure and PTSD Symptom Severity: Assessing Avoidant Coping as a Mediator - Schackner, Jennifer N. (Journal of interpersonal violence, 2021)
Women’s experiences of negative social reactions to disclosure of intimate partner violence (IPV) victimization have been linked to greater posttraumatic stress disorder (PTSD) symptom severity. However, research has not identified factors that may explain this association. The goal of the current study was to extend research in this area by elucidating the potential mediating role of avoidant coping in the relations among negative and positive social reactions to IPV disclosure and PTSD symptom severity. Participants were 173 community women currently experiencing IPV who disclosed their victimization to another individual (M age = 36.31, 65.9% African American). Findings revealed that IPV-victimized women who experienced greater negative social reactions to IPV endorsed higher levels of avoidant coping and greater PTSD symptom severity. Moreover, avoidant coping was found to mediate the negative social reactions–PTSD symptom severity association. Results highlight the relevance of avoidant coping to the link between negative social reactions to IPV disclosure and PTSD symptom severity, and suggest that prevention and intervention efforts targeting avoidant coping may be useful in reducing PTSD symptom severity among IPV-exposed women who experience negative social reactions to IPV disclosure.